Healthcare resource utilization in patients with myeloproliferative neoplasms: A Danish nationwide matched cohort study. (26th August 2022) - Christensen, Sarah Friis; Svingel, Lise Skovgaard; Kjærsgaard, Anders; Stenling, Anna; Darvalics, Bianka; Paulsson, Björn; Andersen, Christen Lykkegaard; Christiansen, Christian Fynbo; Stentoft, Jesper; Starklint, Jørn; Severinsen, Marianne Tang; Clausen, Mette Borg; et al.
Abstract: Few studies have assessed healthcare resource utilization (HRU) in patients with Philadelphia‐negative myeloproliferative neoplasms (MPN) using a matched cohort design. Further, no detailed assessment of HRU in the years preceding an MPN diagnosis exists. We conducted a registry‐based nationwide Danish cohort study, including patients with essential thrombocythemia, polycythemia vera, myelofibrosis, and unclassifiable MPN diagnosed between January 2010 and December 2016. HRU data were summarized annually from 2 years before MPN diagnosis until emigration, death, or end of study (December 2017). We included 3342 MPN patients and 32 737 comparisons without an MPN diagnosis, matched on sex, age, region of residence, and level of education. During the study period, the difference in HRU (rate ratio) between patients and matched comparisons ranged from 1.0 to 1.5 for general practitioner contacts, 0.9 to 2.2 for hospitalizations, 0.9 to 3.8 for inpatient days, 1.0 to 4.0 for outpatient visits, 1.3 to 2.1 for emergency department visits, and 1.0 to 4.1 for treatments/examinations. In conclusion, MPN patients had overall higher HRU than the matched comparisons throughout the follow‐up period (maximum 8 years). Further, MPN patients had substantially increased HRU in both the primary and secondary healthcare sector in the 2 years preceding the diagnosis.